THE USE OF AUTHENTIC MATERIALS IN TEACHING READING COMPREHENSION - Yanuarti Apsari (STKIP Siliwangi, 2014)
Teachers often have difficulties in finding the appropriate learning materials in teaching reading. Without appropriate reading texts that suit them, students spend long hours in the classroom with poor achievement in reading comprehension. This research, therefore aims to find out whether the use of the authentic material can improve students’ reading comprehension. With regard to the purpose of the research, an experimental research is applied where twenty-five pairs of students from two groups are observed. The data are obtained from pre-test and post-test. The data are statistically analyzed and then compared by using mann whitney U test. The result of the study reveals that the use of authentic material in teaching reading does not significantly improve students’ reading comprehension. Nevertheless, it is recommended that teachers use authentic reading materials for a change. In addition, when bringing authentic materials into classroom, they should be used in accordance with students' ability, as well as with suitable tasks being given. Keywords: Authentic Material and Reading Comprehension